Investigating Pb diffusion across buried interfaces in Pb(Zr0.2Ti0.8)O3 thin films via time‐of‐flight secondary ion mass spectrometry depth profiling. (30th June 2017) - Mangum, John S.; Podowitz‐Thomas, Stephen; Nikkel, Jason; Zhou, Chuanzhen; Jones, Jacob L.
Abstract : The diffusion of Pb through Pb(Zr0.2 Ti0.8 )O3 (PZT)/Pt/Ti/SiO2 /Si thin film heterostructures is studied by using time‐of‐flight secondary ion mass spectrometry depth profiling. The as‐deposited films initially contained 10 mol% Pb excess and were thermally processed at temperatures ranging from 325 to 700°C to promote Pb diffusion. The time‐of‐flight secondary ion mass spectrometry depth profiles show that increasing processing temperature promoted Pb diffusion from the PZT top film into the buried heterostructure layers. After processing at low temperatures (eg, 325°C), Pb + counts were low in the Pt region. After processing at elevated temperatures (eg, 700°C), significant Pb + counts were seen throughout the Pt layer and into the Ti and SiO2 layers. Intermediate processing temperatures (400, 475, and 500°C) resulted in Pb + profiles consistent with this overall trend. Films processed at 400°C show a sharp peak in PtPb + intensity at the PZT/Pt interface, consistent with prior reports of a Pt3 Pb phase at this interface after processing at similar temperatures.